Peran Asuransi Terhadap Resiko Pembiayaan - Dewi Puspita; Harto A. Satyo; Rakhmat Rakhmat (Jurnal Mahkamah : Kajian Ilmu Hukum Dan Hukum Islam, 2018)
This research review of the role of insurance against the risk of financing .Research is interesting to be discussed in depth using approach or in depth interviews with employees bmt. To overcome loss arising , people develop a mechanism that at present we know as insurance Hence the institutions of baitul maal wat tamwil need to readiness to at risk of , whether it is the risk of self soul and business risk who traveled. The purpose of this research to know what part insurance against the risk of loans for bmt Mekar Abadi Kota Gajah .The benefits of this research into account and evaluation in their policy for the practitioners of insurance in bmt in solving the about the role of insurance against the risk of financing .This is the kind of research field research ( file risearch ) .The qualitative method was used in the study , a source of primary data in this research is the director , managers and marketing bmt bloom perennial central city an elephant lampung. The result of this research is this insurance Syari’ah on bmt Mekar Abadi was a mutually cooperate ( ta’awun ) and protect ( takafuli ) of the participants insured amelalui the formation of a collection of funds ( funds tabarru’ ) managed in accordance with the principle of worship syari’ah to run the risk of certain. The Insurance in bmt Mekar Abadi for customers that is to guarantee repayment loans / financing as much as plafond initial credit / insured when participants had died sick or accident happened in the insurance (coverage fixed).The Writer advise for cooperatives Mekar Abadi Kota Gajah should improve services that customers feel safe and are satisfied in cooperation with cooperatives Mekar Abadi.